2003
DOI: 10.1128/iai.71.10.6019-6026.2003
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pyogenesInfection Induces Septic Arthritis with Increased Production of the Receptor Activator of the NF-κB Ligand

Abstract: Bacterial arthritis is a rapidly progressive and highly destructive joint disease in humans, with Staphylococcus aureus and Neisseria gonorrhoeae the major causative agents, although beta-hemolytic streptococci as well often induce the disease. We demonstrate here that intravenous inoculation of CD-1 mice with the group A streptococcus (GAS) species Streptococcus pyogenes resulted in a high incidence of septic arthritis. Signs of arthritis emerged within the first few days after injection, and bacterial examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…The capacity of S. pyogenes to cause arthritis as well as lethal disease has been studied in mouse model systems using i.v. inoculation doses of 2 ϫ 10 8 to 4 ϫ 10 8 cells per mouse (40). To study the in vivo impact of CD46, we challenged CD46 transgenic mice and nontransgenic mice with 3 ϫ 10 8 S. pyogenes cells i.v.…”
Section: Resultsmentioning
confidence: 99%
“…The capacity of S. pyogenes to cause arthritis as well as lethal disease has been studied in mouse model systems using i.v. inoculation doses of 2 ϫ 10 8 to 4 ϫ 10 8 cells per mouse (40). To study the in vivo impact of CD46, we challenged CD46 transgenic mice and nontransgenic mice with 3 ϫ 10 8 S. pyogenes cells i.v.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies support the concept that decoy receptors are beneficial during inflammatory responses. In a model of Streptococcus pyogenes-induced arthritis in mice, the presence of osteoprotegerin, a decoy receptor for receptor activator of NF-B ligand, prevented bone destruction in the infected joints (41). In another inflammation model in which Fas ligand-induced lung inflammatory injury was studied, the presence of the decoy receptor 3 analog reduced PMN recruitment into the alveolar compartment and inhibited the appearance in bronchoalveolar lavage fluids of proinflammatory chemokines (42).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the RANKL-RANK-OPG system in inflammation-induced bone loss is demonstrated by the observation that OPG treatment decreases local bone loss in experimentally induced periodontitis and arthritis (23,43,46,55,59). In inflammation-induced local bone resorption, it has been suggested that RANKL is expressed by resident osteoblasts, stimulated by proinflammatory cytokines, such as interleukin-1, tumor necrosis factor alpha, or cytokines of the interleukin-6 family (5,26).…”
Section: Discussionmentioning
confidence: 99%